Quality of life after pulmonary stereotactic fractionated radiotherapy (SBRT): Results of the phase II STRIPE trial. (July 2020) - Nestle, Ursula; Adebahr, Sonja; Kaier, Klaus; Gkika, Eleni; Schimek-Jasch, Tanja; Hechtner, Marlene; Momm, Felix; Gaertner, Jan; Becker, Gerhild; Grosu, Anca-Ligia
Highlights: Prospective data on QoL after pulmonary SBRT of patients with small lung nodules. Long-term preservation of QoL after pulmonary SBRT. First trial revealing QoL-benefit for lung-SBRT patients with low initial QoL-score. Long-term QoL-benefit for frail patients encourages lung-SBRT in such patients. For lung-SBRT 3X12.5 Gy to 60% isodose is efficient and well tolerated. Abstract: Background and purpose: Preserving health related quality of life (HRQOL) plays an important role in considering stereotactic body fractionated radiotherapy (SBRT). The prospective monocenter phase II STRIPE trial investigated long-term HRQOL after SBRT, efficacy and toxicity. Materials and methods: Patients with ≤2 pulmonary lesions ≤5 cm were treated with 4DPET/CT-based SBRT (3 × 12.5 Gy or risk-adapted 5 × 7 Gy, to 60% isodose). Follow up (FU) was performed 2 and 7 weeks after SBRT, then 3-monthly for 2 years with assessment of response (primary endpoint: 2-year cumulative incidence of local progression (LP); secondary endpoints: local progression free survival (LPFS), overall survival (OS) and toxicity (CTCAE)). Impact of predefined patient and treatment related factors on HRQOL (EORTC QLQ-C30 and EORTC QLQ-LC13) was evaluated. Results: Between 02/2011 and 11/2014, 100 patients were given SBRT for 56 NSCLC and 44 pulmonary metastases (M1). Long-term FU overall revealed stable Quality of Life (QoL)/Global health status (GHS), functions-scores and symptoms. For QoL/GHS, patients with low (<median) initial QoL/GHS-Score revealed significantly stronger improvement than those with good QoL/GHS-scores ( p  < 0.001). Probability for LP, LPFS and OS 2 years after SBRT was 8.1% (NSCLC: 7.3%, M1:9.2%), 53.3% (NSCLC: 50.7%, M1: 56.0%) and 62.2% (NSCLC: 57.2%, M1: 68.4%). ≥G3-Toxicity was <4%, but ≥G3 dyspnea was 6% at baseline and 14.5% 2 years after SBRT. Conclusions: These prospective data on representative pulmonary SBRT patients confirm stable preservation of HRQOL after SBRT and demonstrate a QoL/GHS-benefit for patients with low initial QoL/GHS-scores, the regimen of 3 × 12.5 Gy SBRT being efficient and well tolerated. This result may inform shared decision making when discussing SBRT for frail patients.